Development of graphical user interface for lightning risk assessment by using Matlab / Mohd Azrol Shaari - Shaari, Mohd Azrol (2014)
This paper presents the development of graphic user interface for lightning risks assessment for a structure. The goal of this research to identify characteristic of lightning structure and evaluated the lightning risk assessment level. This paper presents the development of lightning risk assessment by using Matlab. The goal of this research is to evaluate the lightning risk level. The risk analysis for the structure is based on Malaysian Standard (MS EC 62305-2). Software has been developed to analyze the lightning risk to the structure. This tool provides interactive and simplifies interface for user to perform the analysis. It is also designed for a user to view lightning risk assessment results of structure and thus will facilitate the user to verify their manual calculation of risk management.